EXPLORING THE HISTORICAL EVOLUTION OF POP MUSIC IN PAKISTAN: A DIACHRONIC PERSPECTIVE - Sana Zafar; Muhammad Farukh Arslan; Hira Haroon (International Journal of Contemporary Issues in Social Sciences, 2024)
Pakistani pop music is a captivating genre which serves as a medium to express cultural values and social issues of Pakistani society through artistic expressions. This study diachronically analyzed the Pakistani pop music across three different eras; the early pop, the film music, and the rise of independent pop respectively. The cultural hegemony proposed by Antonio Gramsci (1971) was taken as framework to examine the relationship between power dynamics, music and culture and to analyze the influence of socio-political aspects on the themes of pop songs. The different pop songs from different eras were taken through audio files, lyrics and music videos for content analysis. The findings of the study revealed the significant changes in themes of Pakistani pop music over the course of time. The thematic evolution explored the cultural and social changes and exposed the relationship between music, culture, and politics. The study contributed in the enhancement of knowledge regarding Pakistani pop music’s thematic development, reasons for its evolution through different periods, and its crucial role in expressing the societal changes.